2023
DOI: 10.1111/sms.14328
|View full text |Cite
|
Sign up to set email alerts
|

The incidence rate of ACL injuries and ankle sprains in basketball players: A systematic review and meta‐analysis

Abstract: Objective To quantify the incidence rate of anterior cruciate ligament (ACL) injuries and ankle sprains according to player sex, playing level, and exposure setting (training vs. games) in basketball players. Methods PubMed, MEDLINE, Google Scholar, and ScienceDirect were searched. Only studies reporting the number of ACL injuries and/or ankle sprains alongside the number of athlete‐exposures (training sessions and/or games) in basketball players were included. Results Thirty studies (17 reporting ACL injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 95 publications
0
2
0
2
Order By: Relevance
“…Las zonas anatómicas con mayor frecuencia de lesiones fueron el tobillo y la pierna. Esto es concordante con la mayoría de los estudios epidemiológicos en esta población (Andreoli et al, 2018;Stojanović et al, 2023). Súbitas inversiones, rotaciones internas y baja flexión plantar de tobillo o el contacto con el pie de un adversario durante acciones de aterrizaje parecen ser los mecanismos que explican su alta frecuencia (Panagiotakis et al, 2017).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Las zonas anatómicas con mayor frecuencia de lesiones fueron el tobillo y la pierna. Esto es concordante con la mayoría de los estudios epidemiológicos en esta población (Andreoli et al, 2018;Stojanović et al, 2023). Súbitas inversiones, rotaciones internas y baja flexión plantar de tobillo o el contacto con el pie de un adversario durante acciones de aterrizaje parecen ser los mecanismos que explican su alta frecuencia (Panagiotakis et al, 2017).…”
Section: Discussionunclassified
“…Con relación a este primer paso, se han encontrado incidencias de lesiones en adolescentes jugadores de básquetbol que van desde 2,64 a 14,4 lesiones/1000 horas de exposición (Owoeye et al, 2020;Pasanen et al, 2017). Las características de estas lesiones van desde agudas, como esguinces de tobillo (Pasanen et al, 2017), roturas de ligamento cruzado (Stojanović et al, 2023) o contusiones en la cabeza (Zynda et al, 2022) a lesiones de origen gradual como tendinopatías en rodilla (Owoeye et al, 2020). Estas lesiones pueden tener distintos grados de severidad, desde lesiones leves sin pérdida de tiempo deportivo, como abrasiones en la piel, a otras más graves, que pueden dejar como consecuencia al deportista, un periodo prolongado de recuperación y, por ende, sin entrenamientos o competencias (Allen et al, 2019).…”
Section: Introductionunclassified
“…It usually happens when the foot is rolled inward, either from a misstep or from an attack. Some authors reported different values for ankle injuries: 11%; 15%; 22%; 32%; 23% (for both men and women) [93][94][95][96][97], and the results of the National Collegiate Athletic Association indicate 20% for men and 21% for women (adolescents). These values differ from our findings of 15.84 ± 3.93% for professionals and 17.99 ± 3.63% for amateurs.…”
Section: The Location Of the Injuriesmentioning
confidence: 99%
“…Another systematic review has recently explored the pooled incidence rates of anterior cruciate ligament injuries among basketball players. Almost 93% of the included studies were developed by authors with institutional affiliations in the same country 10. In this context, SEM readers may have a better perception of the directness of the evidence if GRADE had been used.…”
Section: Indirectness In Gradementioning
confidence: 99%